Building Community Health Literacy to Achieve Health Equity: Insights from Ethiopian Tewahedo Social Services Community Leader in a County-Level Health Literacy Initiative (Health Equity, 2023)
This perspectives article shares insights from a county-level project in Franklin County, Ohio, to build collective organizational health literacy (HL) capacity across new sustainable networks to advance community-level HL. We provide an overview of the initiative followed by specific insights from a cultural liaison, the article's first author, who works in a community-based organization. He shares his collectivist perspective in building HL capacity at the grassroots level toward community-level goals. A shift in focus from individual responsibility to collective impact represents an important mindset change for attaining HL and builds on community strengths and values toward health equity.